Analysis of technological process efficiency of sugar beet cultivation based on simulation method - Volokha, M. P. (НУБіП України, 2018)
The paper considers the technological process of sugar beets cultivation as a single object of modeling. The aim is to investigate the interrelation of separate technological operations and evaluate the technological efficiency of the beet cultivation. The study of technological processes based on the simulation allows us to investigate interconnections, to highlight technical and economic indicators, to evaluate the impact on profitability, to determine the directions of development and ways to improve the technical and technological basis of the beet production industry.
Аналіз технологічної ефективності процесу обробітку цукрових буряків на основі методу моделювання
У статті розглядається технологічний процес вирощування цукрових буряків як єдиний об'єкт моделювання. Мета дослідження-вивчити взаємозв'язок окремих технологічних операцій і оцінки технологічної ефективності вирощування цукрових буряків. Вивчення технологічних процесів на основі імітаційного моделювання дозволяє до сліджувати взаємозв'язки, виділити технікоекономічних показників, оцінити вплив на рентабельність, визначити напрямки розвитку та шляхи вдосконалення технічної і технологічної основи виробництва цукрових буряків.
Keywords: sugar beets; technological process; technical tool; simulation; pre-sowing tillage; технологічний процес; цукрові буряки; технічні засоби; моделювання; передпосівної обробки грунту